2016
DOI: 10.1039/c6nr00926c
|View full text |Cite
|
Sign up to set email alerts
|

Gallium plasmonic nanoparticles for label-free DNA and single nucleotide polymorphism sensing

Abstract: A label-free DNA and single nucleotide polymorphism (SNP) sensing method is described. It is based on the use of the pseudodielectric function of gallium plasmonic nanoparticles (GaNPs) deposited on Si (100) substrates under reversal of the polarization handedness condition. Under this condition, the pseudodielectric function is extremely sensitive to changes in the surrounding medium of the nanoparticle surface providing an excellent sensing platform competitive to conventional surface plasmon resonance. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…e) Energy shifts (δE) in pseudodielectric function (〈εi〉) spectra for HP2C, HP2SNP, and HP2NC (up) and correlation between δE and the concentration in case of HP2C (bottom). Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…e) Energy shifts (δE) in pseudodielectric function (〈εi〉) spectra for HP2C, HP2SNP, and HP2NC (up) and correlation between δE and the concentration in case of HP2C (bottom). Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Applicationmentioning
confidence: 99%
“…Marin et al demonstrated the use of a label‐free sensor based on plasmonic Ga NPs for detecting DNA, single nucleotide polymorphisms (SNPs), and gene mutation via ellipsometric measurement. They used GaNP/Si as a sensing platform due to the high sensitivity of the pseudodielectric function (〈ε i 〉) of Ga, as illustrated in Figure d.…”
Section: Applicationmentioning
confidence: 99%
“…We have optimized the RPH angle for the as-grown and oxidized samples before and after functionalization being 45º and 52.5º respectively. This condition gives a characteristic lineshape in the <ε 2 > with a maximum peak-to-peak amplitude 16 . Figure 5(a) shows the SE measurements of a 400 min oxidized sample before and after functionalization with 100 mM of MCH.…”
Section: Mch Concentration (Mm)mentioning
confidence: 99%
“…Regarding biosensing, our group has been widely investigating the detection of different biomolecules such as glutathione 15 , Helicobacter pylori and specific gene mutation related to disease such as cystic fibrosis 16 . These works analyzed the optical properties of the Ga NPs by spectroscopic ellipsometry (SE) before and after the functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…Other materials were also explored as substrates for localized plasmons, like gallium NP whose resonance can be tuned from the UV to the infrared range by varying their shape and size. By exploiting a condition of reversal of polarization handedness as measured through ellipsometry, it was possible to detect DNA strands of 10-100 nt with 20 pg/ml LOD, also discriminating single nucleotide mismatches [70].…”
Section: Na In the Crosshairs: Label-free Detection Of Specific Sequementioning
confidence: 99%